Analisia Pengaruh Pemikiran Usul Dan Fiqh: Karya Syeikh Muhammad Tahir Jalaluddin: The Influence of Legal and Jurisprudential Thought: The Work of Sheikh Muhammad Tahir Jalaluddin - Abdul Hamid, Faisal @ Ahmad Faisal; Abdul Malik, Mohd Puaad (Al-Basirah Journal, 2021)
Sheikh Muhammad Tahir Jalaluddin is a prominent Malay scholar who has produced several works in various fields such as jurisprudence, astronomy, preaching, and education. However, he did not specifically write a book on the principles of jurisprudence Nevertheless, his work titled Ta’yid Tadhkirah Muttabi‘ al-Sunnah fi al-Rad ‘Ala al-Qa’il bi Sunniyyah Rak‘atain Qabl al-Jum‘ah validates his position as a highly skilled and expert in that field. This article will analyze the influence of his usul and fiqh thoughts in the book. His mindset is evident because of his deep understanding and mastery of the science of usul which is the most basic matter and the only method to publish questions for fiqh law. He reminded that Islam is very encouraging to think because there are many verses of the Qur’an that call for the use of reason, especially in the matter of understanding the content of the Qur’an and al-Sunnah.